PEER FEEDBACK ON LANGUAGE FORM IN TELECOLLABORATION - Paige Ware; Robert O'Dowd (Language Learning and Technology)
We performed a two-phase, year-long research project that explored the impact of peer feedback on language development. We investigated specifically how and when post-secondary learners of English and Spanish provide corrective feedback on their partners' use of the target language in weekly asynchronous discussions by assigning them to one of two conditions: e-tutoring, in which students were asked to provide peer feedback on any linguistic form they perceived as incorrect; and e-partnering, in which students were not required to provide peer feedback but could do so on their own initiative. We examined the frequency and type of language use by coding the feedback for language-related episodes (Swain & Lapkin, 1998) and for feedback strategies (Ros i Solé & Truman, 2005). The findings indicate that students in both conditions preferred an inclusion of feedback on form as part of their exchange, but such feedback only occurred when explicitly required in the e-tutoring condition. Pedagogical implications include the need to situate peer feedback on form within current models of telecollaboration and to assist students in using feedback strategies such as reformulations, which do not rely on a deep understanding of the target or native language grammar.